Supermicrosurgery: History, Applications, Training and the Future - Badash, Ido; Gould, Daniel J.; Patel, Ketan M. (Frontiers in Surgery, 2018)
Supermicrosurgery, a technique of dissection and anastomosis of small vessels ranging from 0.3 to 0.8mm, has revolutionized the fields of lymphedema treatment and soft tissue reconstruction. The technique offers several distinct benefits to microsurgeons, including the ability to manipulate small vessels that were previously inaccessible, and to minimize donor-site morbidity by dissecting short pedicles in a suprafascial plane. Thus, supermicrosurgery has become increasingly popular in recent years, and its applications have greatly expanded since it was first introduced 20 years ago. While supermicrosurgery was originally developed for procedures involving salvage of the digit tip, the technique is now routinely used in a wide variety of microsurgical cases, including lymphovenous anastomoses, vascularized lymph node transfers and perforator-to-perforator anastomoses. With continued experimentation, standardization of supermicrosurgical training, and high quality studies focusing on the outcomes of these novel procedures, supermicrosurgery can become a routine and valuable component of every microsurgeon’s practice.